2010
DOI: 10.4061/2010/790539
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Coronary Artery Disease

Abstract: Coronary artery disease (CAD) is a multifactorial disease with environmental and genetic determinants. The genetic determinants of CAD have previously been explored by the candidate gene approach. Recently, the data from the International HapMap Project and the development of dense genotyping chips have enabled us to perform genome-wide association studies (GWAS) on a large number of subjects without bias towards any particular candidate genes. In 2007, three chip-based GWAS simultaneously revealed the signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Massive genome-wide-association studies (GWAS) and meta-analysis have been performed to identify common gene variants that influence susceptibility to CAD. So far, about 28 loci have been have been identified among Caucasians and African Americans [73,74,75,76,77,78,79,80]. Some of these loci are also associated with risks for other diseases and traits.…”
Section: Genome Wide Association Studiesmentioning
confidence: 99%
“…Massive genome-wide-association studies (GWAS) and meta-analysis have been performed to identify common gene variants that influence susceptibility to CAD. So far, about 28 loci have been have been identified among Caucasians and African Americans [73,74,75,76,77,78,79,80]. Some of these loci are also associated with risks for other diseases and traits.…”
Section: Genome Wide Association Studiesmentioning
confidence: 99%
“…Until now, many single-nucleotide polymorphisms (SNPs) of candidate genes as well as of regulatory loci have been discovered (Ogawa et al, 2010;The IBC 50K CAD Consortium, 2011). In 2007, independent genome-wide association studies revealed nine highly correlated SNPs (r 2 > 0.8) in a new locus in the region of chromosome 9 (9p21.3), showing the greatest association with heterogeneous CAD of all of the loci analyzed so far (Helgadottir et al, 2007;McPherson et al, 2007;Samani et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several gene variants have been related to cardiovascular risk or risk factors [25], [26]. However, this may be the first time that genetic variation in the vitamin C transporter gene SLC23A2 is tested in relation to cardiovascular disease, hence the results require replication.…”
Section: Discussionmentioning
confidence: 97%